Improved Hydrogen Oxidation Reaction Activity and Stability of Buried Metal-Oxide Electrocatalyst Interfaces - Speck, Florian D.; Ali, Farhan S. M.; Paul, Michael T. Y.; Singh, Ramesh K.; Böhm, Thomas; Hofer, André; Kasian, Olga; Thiele, Simon; Bachmann, Julien; Dekel, Dario R.; Kallio, Tanja; Cherevko, Serhiy (Chemistry of Materials, 2020)
Various bifunctional metal-oxide composites have recently been proposed as advanced hydrogen oxidation reaction (HOR) electrocatalysts for anion-exchange membrane fuel cells (AEMFCs). It is postulated that metal and oxide are active sites for the adsorption of hydrogen/proton and hydroxide ions, respectively. Of particular interest are the so-called buried interfaces. To investigate processes governing activity and stability at such interfaces, we prepare model Pd and Pt electrocatalysts which are fully covered by thin CeOx films. We investigate how oxide thickness influences HOR activity and dissolution stability of the electrocatalysts. It is found that materials behave very differently and that only Pd exhibits an enhanced HOR activity, while both oxide-protected metals are more stable toward dissolution. A 10-fold decrease in dissolution and 15-fold increase in HOR exchange current density are demonstrated for the optimized Pd/CeOx composites in comparison to pure Pd. We assess the mechanism of the electrocatalytic improvement as well as the role of the protective oxide films in such systems through advanced electrochemical and physical analysis. It is highlighted that a uniform, semipermeable oxide layer with a maximized electrocatalyst-oxide interface is crucial to form HOR catalysts with improved activity and stability.
CRIS-Team WoS Importer:2020-10-23